2022
DOI: 10.3389/fendo.2022.890941
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Up-Regulated ANXA3 Resulting in Fracture Non-Union in Patients With T2DM

Abstract: Diabetes mellitus is a metabolic disorder that increases fracture risk and interferes with bone formation and impairs fracture healing. Genomic studies on diabetes and fracture healing are lacking. We used a weighted co-expression network analysis (WGCNA) method to identify susceptibility modules and hub genes associated with T2DM and fracture healing. First, we downloaded the GSE95849, GSE93213, GSE93215, and GSE142786 data from the Gene Expression Omnibus (GEO) website, analyzed differential expression genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
(68 reference statements)
0
4
1
Order By: Relevance
“…It is worth noting that studies have shown that osteoporosis and diabetes are risk factors for fracture nonunion 45,46 ; however, the results of this study suggest the lack of a significant association, possibly due to the study population. These factors are mostly observed in elderly individuals, whereas femoral shaft fractures are mostly caused by high-energy injuries.…”
Section: Discussioncontrasting
confidence: 77%
“…It is worth noting that studies have shown that osteoporosis and diabetes are risk factors for fracture nonunion 45,46 ; however, the results of this study suggest the lack of a significant association, possibly due to the study population. These factors are mostly observed in elderly individuals, whereas femoral shaft fractures are mostly caused by high-energy injuries.…”
Section: Discussioncontrasting
confidence: 77%
“…Furthermore, GO analysis revealed that bosutinib mainly influences extracellular structure organization, extracellular matrix organization, sterol biosynthetic process, secondary alcohol biosynthetic process, and cholesterol biosynthetic process (Figure B). Pathways enrichment analysis using GO and KEGG revealed several pathways related with bone metabolism or bone-related disease, including extracellular matrix organization, steroid biosynthesis, TNF signaling pathway, as well as starch and sucrose metabolism. − PCA showed that the difference between groups is obvious (Figure S1D). Venn diagram analysis revealed that 382 and 297 genes were specifically expressed in hUCMSCs induced with and without bosutinib, respectively, with 10830 genes co-expressed between the two groups (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…MMP9 [262], IGF2 [273], SOCS3 [274], MMP8 [265], OSM (oncostatin M) [266], PLAU (plasminogen activator, urokinase) [275], ADAMDEC1 [269], IL1RN [270], TLR4 [271], CD80 [276] and TXNIP (thioredoxin interacting protein) [272] make great contributions to the progression of nasal polyps. MMP9 [277], S100A12 [278], IGF2 [279], GPR84 [280], SOCS3 [281], ANXA3 [282], IGFBP2 [283], NOS1AP [284], G0S2 [285], HP (haptoglobin) [286], MMP8 [287], SLC6A19 [288], OSM (oncostatin M) [289], S100A8 [290], FFAR3 [291], ARG1 [292], ADM (adrenomedullin) [293], S100A9 [294], NRG1 [295], IL1R1 [296], IL4R [297], TSPO (translocator protein) [298], TXN (thioredoxin) [299], PLAU (plasminogen activator, urokinase) [300], SLC11A1 [301], TRPM2 [302], RETN (resistin) [303], NLRC4 [304], CD55 [305], ALOX5AP [306], GPR160 [307], TRPM6 [308], ALOX5 [309], IL1RN [310], ADM2 [311], DGAT2 [312], TLR4 [313], ENTPD1 [314], GRB10 [315], IL17RA [316], IRS2 [317], MGAM (maltase-glucoamylase) [318], FADS2 [319], SLC22A4 [320], KCNJ15 [321], PPP1R3B [322], CTSD (cathepsin D) [323], SERPINB11 [324], COL4A3 [325], ADAM12 [326], SOX5 [327], CD80 [328], ERBB2 [329], POU2AF1 [330], FASLG (Fas ligand) [331], SOX13 [332], BANK1 [333], IL2RA [334], AQP3 [335], CCR4 [336], CD74 [337], FCRL3 [338], ITGB7 [339],...…”
Section: Discussionmentioning
confidence: 99%